MEMBANGUN INTEGRITAS DAN PRIBADI TANGGUH DENGAN MENELADANI KISAH NABI YUSUF, ANALISIS TERHADAP KONSEP REVOLUSI MENTAL DARI PRESIDEN RI JOKO WIDODO - Husni Adabi; Imam Sukardi (Attaqwa: Jurnal Ilmu Pendidikan Islam, 2022)
This research is the result of library research on Building Integrity and a Tough Person by Imitating the Story of the Prophet Yusuf (Analysis of the Concept of Mental Revolution from the President of the Republic of Indonesia, Joko Widodo). This study aims to emphasize the importance of integrity and a strong personality in one's character, with the example of the story of the prophet Yusuf AS, and to remind people of the concept of mental revolution echoed by the President of the Republic of Indonesia, Joko Widodo. The type of research used is library research. The descriptions used are descriptive analytic, which is by collecting existing data, interpreting, and conducting interpretive analysis. The approach used in this research is a philosophical and pedagogical approach. With this philosophy, problem solving is investigated rationally through directed reasoning with a textual analysis style that is oriented towards efforts to formulate ideas through interpretation of the text. Meanwhile, the pedagogical approach here is to try to explain in more detail the existing concepts using educational theory. In general, the formation of integrity and strong personalities is carried out most effectively by exemplary methods. While a good and obedient role model is to be an example, of course, from a noble figure, from the best story in the al-Qur'an, namely the story of Prophet Yusuf AS Prophet Yusuf's life was full of tests. He went through the various trials of life with full wisdom. At its peak, Allah made Prophet Yusuf a chosen person whose life inspired those who came after him. His life story is studied and researched by scholars, scientists and scholars. There are many lessons that we can take both implied and implicit from the story of the Prophet Yusuf for us in building a superior personality to achieve a successful life. To become a developed and modern country with a superior society, various reforms need to be carried out. In other words a mental revolution. It aims to make various human mentalities, both individually and collectively, experience fundamental changes. One of the effective strategies in providing understanding and application of mental revolution is by exemplary, such as the integrity and tough personality exemplified by the Prophet Yusuf. In education, giving examples is very emphasized because the behavior of an educator gets special observations from students. Therefore, it is very important for educators and public figures to have integrity and a strong personality as role models and direction providers in realizing the concept of mental revitalization. So that later it will give birth to a generation who are not only smart in the fields of science and technology, but also have good morals through Islamic Religious Education from the example of the story of the Prophet Yusuf.